Proceedings of the 16th International Seminar on Paste and Thickened Tailings 2013
DOI: 10.36487/acg_rep/1363_29_hasan
|View full text |Cite
|
Sign up to set email alerts
|

Full scale experiments on the effectiveness of a drainage system for cemented paste backfill

Abstract: This paper presents full-scale experiments on cemented paste backfilling in two operating mine stopes located at Raleigh mine, Kalgoorlie, Western Australia. The experiments compared the behaviour of the cemented paste backfill (CPB) in a drained stope and an undrained stope. The drained stope was equipped with a drainage system at the barricade, whereas the undrained stope was not. Total stress and pore water pressure sensors were installed to measure the stress within the fill mass during and after backfilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…This anomalous behaviour has been observed a number of times and should not be dismissed as instrument malfunction, remembering that it has also been reported by other workers (Thompson et al 2012;Hasan et al 2013). Importantly, it is not recorded by the piezometers.…”
Section: Backfillingsupporting
confidence: 69%
See 3 more Smart Citations
“…This anomalous behaviour has been observed a number of times and should not be dismissed as instrument malfunction, remembering that it has also been reported by other workers (Thompson et al 2012;Hasan et al 2013). Importantly, it is not recorded by the piezometers.…”
Section: Backfillingsupporting
confidence: 69%
“…It is unclear why this occurs. Other in-stope surveys (Thompson et al 2012;Hasan et al 2013) observed the same phenomenon. After 3.7 days, the vertical stress cell displayed erroneous readings, indicating likely physical damage of the sensor (shown as a 'star' symbol in Figure 10b).…”
Section: Backfillingsupporting
confidence: 67%
See 2 more Smart Citations
“…Thompson et al 2011) and the University of Western Australia (e.g. Helinski et al 2011;Hasan et al 2013) to collect in-stope measurements of pore pressure, total stress and temperature. An ability to back−analyse these stopes with realistic numerical models is essential for meaningful interpretation and ultimately the development of tools to facilitate backfill management.…”
Section: Introductionmentioning
confidence: 99%